Locomotor Skills: Traditional Games in the Fundamental of Physical Activities - Irawan, Fajar Awang; Sutaryono, Sutaryono; Permana, Dhias Fajar Widya; Chuang, Long-Ren; Yuwono, Yuwono (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2021)
Motor coordination will be hampered if the stimulation of children's movement development tends to be neglected. This will have an impact on the child's movement skills. The purpose of this study was to determine traditional games in basic physical activities using locomotor skills. This study uses Classroom Action Research (PTK) which aims to see how much increase in the application of traditional games. The research was conducted at Madrasah Ibtidaiyah Lerep Ungaran Barat and this study used male students aged 7-9 years. There were 18 children who followed and participated in traditional games in this study. Only 8 children scored 44-62 and 10 children scored 63-81, so there were still some children who had not developed according to expectations in cycle I. Basic locomotor skills in cycle II obtained the developing category according to expectations. totaled 3 children and Very Good Development as many as 15 children. Activities carried out by children can increase stimulation and can develop movement skills to improve children's motor skills. The data on basic locomotor motion skills in pre-cycle is 33% in the Undeveloped category. In the first cycle, 45% was found in the Start Developing category and in the second cycle it was 83% in the Very Developed category. This study found that traditional games are suitable for the development of fundamental locomotor skills. Future research can add to children's physical fitness activities that can monitor their increase in physical abilities.